Comment on “Solution of Schrödinger equation for two different potentials using extended Nikiforov-Uvarov method and polynomial solutions of biconfluent Heun equation” [J. Math. Phys. 59, 053501 (2018)] - Fernández, Francisco Marcelo (2021)
We analyze some polynomial solutions to the Schrödinger equation with a central-field potential derived recently by means of the so-called extended Nikiforov-Uvarov method. We show that this approach does not produce the spectrum of the non-relativistic quantum-mechanical model but merely some eigenvalues for particular values of the model parameters. In addition, the approach just mentioned appears to overlook the restrictions that reveal the problem as conditionally solvable.